Nutrition in mental and physical health - Zavitsanou, Aggeliki; Drigas, Athanasios (Technium Social Sciences Journal, 2021)
Eating habits are crucial for human health. People around the world have health problems due to their diet. Malnutrition combined with a lack of essential nutrients and obesity with overconsumption of sugar is significant problems. For the most part, the human daily diet should include foods rich in vitamins, fatty acids, minerals, and trace elements. On the other hand, the consumption of substances such as sugar and trans fats causes negative effects on the human body. Fish, vegetables, and nuts are some of the food that contributes to good health. Also, specific foods help the hormones of happiness to increase in our body. This has the effect of reducing stress and increasing happiness. New technologies are a tool that can help individuals to maintain proper nutrition and good health. For example, through the iCTs applications, everyone can individually control his weight, physical exercise, and find the right combinations to have a better and more quality life without diseases.